The Development of Unity. Issue 3 (2nd July 2020) - Wenar, Leif
Abstract: Martha Nussbaum's list of the 10 central capabilities contains the most plausible account of valuable functionings that we have. In this lecture, I explore how Nussbaum's account converges with the deepest explanation of what is intrinsically valuable—what is good in itself. This exploration shows how Nussbaum's account tracks the same logic of value that we find in many of the world's great philosophical traditions. What all of these philosophers are telling us is that goodness is unity: unity with the world, with each other, and within ourselves.